Pedestrian facilities : geometric design for safety and mobility - Schoon, John G. 1937- (ICE Publishing, 2019)
Pedestrian Facilities provides detailed guidance on the design of pedestrian facilities to encourage the safety, comfort and convenience of pedestrians and other road users. The emphasis throughout is on numerical, functional aspects of designing footways, crossings along roads and junctions, roundabouts, and other spaces where pedestrian and vehicular traffic interact. Drawing together a broad range of topics presented across numerous reports and documents, the book also presents design principles which can foster improvements to this guidance and will also provide assistance where unique design solutions are needed. Coverage in this second edition includes updated governmental guidance on pedestrian facilities design; evolution of design for shared space and 'sojourning'; developments in simulation and multi-modal level-of-service quantification; joint pedestrian and bicycle traffic; and implications of the Equality Act.